2022
DOI: 10.1093/ejcts/ezac086
|View full text |Cite
|
Sign up to set email alerts
|

Wearable cardioverter defibrillator multicentre experience in a large cardiac surgery cohort at transient risk of sudden cardiac death

Abstract: OBJECTIVES The wearable cardioverter defibrillator (WCD) is an established, safe, effective solution, protecting patients at risk of sudden cardiac death. We specifically investigated WCD use in cardiac surgery patients since data for this patient group are rare. METHODS Retrospective data analysis in 10 German cardiac surgery centres was performed. Cardiac surgery patients with left ventricular ejection fraction (LVEF) ≤35% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
6
3
0
Order By: Relevance
“…However, our study still gives valuable insight into the efficacy of the WCD in a real‐life setting. Moreover, our study supports the reported findings of a large German multi‐center study (Kuehn et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, our study still gives valuable insight into the efficacy of the WCD in a real‐life setting. Moreover, our study supports the reported findings of a large German multi‐center study (Kuehn et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…In this retrospective analysis from a single cardiac surgery center in Germany, safety, effectiveness, and compliance of WCD use were investigated in patients after cardiac surgery in a real‐life setting. The presented data complement the study results of a recent, large German multi‐center study reported by Kuehn et al (2022)…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations